PENGARUH METODE PEMBELAJARAN PQ4R TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 5 PEKANBARU (Studi Eksperimen Kuasi ) - Yuli Heltiza; Zariul Antosa; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the low learning outcomes of IPS obtained by the students. Researchers suspect that one reason is the learning method used is still teacher-centered and less actively involves students in the learning. One of the methods that can be used is the method PQ4R. Learning methods PQ4R is a method of learning that can engage students actively in developing science as a whole, give the opportunity to students to acquire and understand the knowledge directly, as well as the learning process becomes memorable and long lasting in the memory of the students that can help students understand and improve student's ability in the given subject matter. The type of this research is experiment quasi with the research design randomized pretest-posttest control group design . The population of this research is students of class IV Elementary school 5 Pekanbaru. The sample in this research is class IVA as the experimental class and class IVB as the control class. Data collection was carried out by using test method. The results data of the study were then analyzed by performing the test prerequisites that include normality test, homogeneity test, and t-test. Based on the results of data analysis obtained the influence of the learning method PQ4R in the experimental class is at 71% but on the test the difference significance mean (t-test) the experimental class with the control class in the get t count ≤ t table or 0,16 ≤ 2,013 thing is that there is no difference in learning outcomes significantly between the control class with the class experiment. So the hypothesis in this research is there is influence of learning method PQ4R against social studies learning out comes of student s grade 4 elementary school 5 Pekanbaru.Key Words: PQ4R learning method, social studies learning outcomes.